1998
DOI: 10.1093/rheumatology/37.9.972
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of serum and urinary nitrate levels in patients with systemic lupus erythematosus

Abstract: In SLE, serum and urinary nitrate levels do not parallel lupus activity. Other variables, related or not to SLE, seem to affect these levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
1
14
1
Order By: Relevance
“…This lack of effect of nebivolol on the serum NO metabolites level in the present study suggests either that the observed increase in GFR 6 months after angioplasty in nebivolol-treated patients is not mediated by a NO-dependent mechanism or that nitrate-nitrite excretion does not adequately reflect the actual effect of nebivolol in the renal circulation. This latter hypothesis is supported by findings from other clinical conditions [16]. …”
Section: Discussionsupporting
confidence: 79%
“…This lack of effect of nebivolol on the serum NO metabolites level in the present study suggests either that the observed increase in GFR 6 months after angioplasty in nebivolol-treated patients is not mediated by a NO-dependent mechanism or that nitrate-nitrite excretion does not adequately reflect the actual effect of nebivolol in the renal circulation. This latter hypothesis is supported by findings from other clinical conditions [16]. …”
Section: Discussionsupporting
confidence: 79%
“…It is readily transformed into nitrate and nitrite, which are excreted into the urine. Several studies have shown elevated levels of NO and/or nitrate/nitrite in the blood (117, 123–127) and urine (125) of lupus patients, with higher levels in patients with active disease. The correlation of serum NO or nitrite levels with disease activity is more variable among studies.…”
Section: Candidate Biomarkers Of Lupus Activitymentioning
confidence: 99%
“…Other studies, however, have not confirmed these observations. Although serum nitrate concentrations showed moderate correlation (r = 0.35) with SLEDAI scores in a univariate cross‐sectional analysis of 50 SLE patients, there was no correlation (r = 0.13) between SLEDAI scores and serum nitrate levels when serial measurements were analyzed (125). No statistically significant correlation between serum nitrite levels and SLEDAI scores was found in a cohort of Chinese patients with (n = 35) or without (n = 37) kidney disease (117).…”
Section: Candidate Biomarkers Of Lupus Activitymentioning
confidence: 99%
“…Definitive data came from two prospective studies looking at NO levels and disease activity. Gonzalez-Crespo et al [18] showed an increase in NO levels and urinary nitrate/creatinine ratio in 50 patients with active SLE compared with inactive patients or healthy control individuals, and Gilkeson et al [19•] reported increased plasma levels of NO and nitrotyrosine in a cohort of 26 patients with SLE. In the first study, the authors could not find a correlation between serum or urinary NO levels and disease activity, although NO determinations may have been influenced by the high rates of infection (24%).…”
Section: Oxidation Nitric Oxide and Endothelium Activation In Systementioning
confidence: 99%